Analisis Implementasi Lean Six Sigma Terhadap Length Of Stay (LOS) di Rumah Sakit: Literatur Review - Shifa Aulia Maghfiroh; Khoirunnisa Ghefira Yusrani; Nurul Aini; Acim Heri Iswanto (Pusat Riset dan Inovasi Nasional, 2023)
Lean is a concept and technique for systems that optimizes patient benefit by decreasing waste and waiting time. The literature review approach is used in this study to acquire research data, with internet searches serving as a supplementary tool while looking for relevant papers. According to the study findings, mean hospital length of stay (LOS) fell by 24% throughout the intervention period in 259 patients with PMV (131 pre-intervention; 128 post-intervention) (29 vs. 22 days, p 0.001). This demonstrates that clinical redesign based on Lean Six Sigma decreases LOS in intensive care units. Other studies show that utilizing Lean Six Sigma has resulted in a 57% reduction in length of stay and an 88% reduction in the identification of non-value added tasks. Lean management in hospitals is a step toward greater service efficiency that has been shown to outperform Total Quality Management (TQM) and Plan, Do, Check, Action (PDCA) improvements. Customers and their families gain from shorter wait times, as do healthcare employees (medical, emergency, and non-medical) and hospital administration. The use of the lean six sigma approach in conjunction with the DMAIC cycle effects LOS reduction, indicating that lean six sigma can reduce LOS in hospitals.